Effect of Different Anti-hypertensive Drugs on Circadian Blood Pressure Profile in Elderly Hypertensive Patients - Bingqing YU; Jinping ZHOU; Zhongxian FENG; Junxia XU (康复学报)
Objective:To explore the effect of different anti-hypertensive drugs on circadian blood pressure profile in elderly hypertensive patients.Methods:Retrospective study was carried out. According to the survey of drug use, 204 elderly hypertension patients who were treated in cadre's wards of Fuzhou General Hospital were divided into five groups: 1) long-acting calcium channel blockers (CCB group)(n=50);2) angiotensin converting enzyme inhibitors (ACEIs) or angiotensinⅡreceptor blockers (ARBs)(AA group)(n=22);3) treated with joint anti-hypertensive scheme including ACEIs or ARBs (but not including diuretics)(AAND group)(n=60);4) treated with joint anti-hypertensive scheme including diuretics (but not including ACEIs or ARBs)(DNAA group)(n=19);5) treated with joint anti-hypertensive scheme including diuretics and ACEIs or ARBs group (DAA group)(n=53), to observe the profile on circadian blood pressure in each group, binary Logistic regression analysis was used to evaluate the correlation between circadian blood pressure profile and its influencing factors.Results:Compared to the CCB group, the level of all day average SBP and daytime SBP in the DAA group were both lower (all P<0.01), the decreasing level of SBP at night in the DAA group was higher (P<0.05). Compared to the AAND group, the levels of SBP at night in the DNAA group was lower (P<0.05), the decreasing level of SBP at night in the DNAA group and the DAA group were both higher (all P<0.05). The abnormal blood pressure rhythm in the DNAA group and the DAA group were 4.26%(6/141) and 12.06%(17/141), significantly better than the 34.04%(48/141) in the CCB group (P<0.01), 14.18%(20/141) in the AA group (P<0.01) and 35.46%(50/141) in the AAND group (P<0.01). Binary logistic regression showed that circadian blood pressure profile had some relation with the factors as age, BMI and strategy of anti-hypertensive drugs. Compared with patients treated with CCB, AA and AAND, the one who was treated with DAA had the tendency of lower incidence of abnormal circadian blood pressure rhythm (OR=0.010, 0.034 and 0.049 respectively, all P<0.001).Conclusion:Different kinds of anti-hypertensive drugs have different effect on circadian blood pressure profile. Joint anti-hypertension strategy is better than individual medication, including that diuretics is an effective treatment strategy to restore the abnormal circadian blood pressure rhythm to normal.